As tramas da des(re)territorialização camponesa: a reinvenção do território veredeiro no entorno do Parque Nacional Grande Sertão-Veredas, Norte de Minas Gerais - Martins, Geraldo Inácio (2011)
The development of this research is to understand the perspective of the encounter between the policies of modernization of agriculture and environmental conservation on the territory of peasants in the north of the state of Minas Gerais. Specifically, it stands for the Settlement Project Aimed at Serra das Araras and the National Brazilian Park Grande Sertão Veredas. We seek to analyze essentially the terms in which this meeting led to dereterritorizalization or reterritorializations, the implications on the territory and its representations and transformations of man-nature relationship. As an empirical reference, the 'locus' of the research is the Settlement Project São Francisco, located in the town of Formoso, in the state of Minas Gerais. Originally, this settlement was created to receive the residents expropriated of their lands by public policies. For this analysis it was crucial a field research, some oral sources and historical documents. These methodologies were important regarding both to the movement of theory, and for understanding the changes and ruptures experienced by those peasants. This thesis makes clear that the processes of deterritorialization were ensued over time. Before those processes this research demonstrates the deterritorialization by the advance of capitalist agriculture and the enclosure of the conservation area. Following, it explains about the Settlement Project São Francisco as a possibility for the reconstruction of territories. In this case there are processes by which becomes difficult the human action, making the deterritorialization prolonged and causing a precarious reterritorialization. Currently, PA São Francisco (Settlement Project São Francisco), a land where it is not even guaranteed as a first territory, reinvent itself as the only way to deal with prolonged deterritorializations and precarious reterritorializations. Keywords: PADSA (Settlement Project Aimed